Cutoff points in STOP-Bang questionnaire for obstructive sleep apnea - NEVES, Jose Apolinário Silva, JUNIOR; FERNANDES, Ana Paula Andrade; TARDELLI, Maria Angela; YAMASHITA, Américo Massafuni; MOURA, Sônia Maria Pereira Guimarães Togeiro; TUFIK, Sérgio; SILVA, Helga Cristina Almeida da (Arquivos de Neuro-Psiquiatria, 2020)
Background: Obstructive Sleep Apnea Syndrome (OSAS) is a public health problem of high prevalence and impacts on quality of life, anesthetic complications and cardiovascular diseases. In view of the difficulty in accessing the polysomnography, it is necessary to validate other methods for OSAS diagnostic screening in clinical practice in our country, such as the STOP-Bang questionnaire. Objective: To validate the STOP-Bang questionnaire in Brazilians and evaluate optimal cutoff points. Methods: After translation and back-translation, STOP-Bang questionnaire was applied to 71 individuals previously submitted to polysomnography and classified into control, mild, moderate or severe OSAS. Results: The majority of patients was male (59.2%), white (79%), aged 48.9±13.9 years, and with neck circumference >40 centimeters (73.8%). STOP-Bang score was higher in OSAS mild (median/inter-quartis 25-75%: 5/3.5-6), moderate (4.5/4-5) and severe (5/4-6), versus control (2.5/1-4). The receiver operating characteristic (ROC) curve indicate that scores 3, 4 and 6, present the best specificity values (100, 80 and 92.9%) with acceptable sensitivity (60, 66.7 and 50%) in the mild, moderate and severe OSAS subgroups, respectively. In OSAS group analysis (Apnea Hypopnea Index [AHI] ≥5, <15, ≥15 - <30, ≥30), STOP-Bang cutoff point of 6 was optimal to detect OSAS. Conclusion: STOP-Bang Brazilian version identified OSAS patients with lower sensitivity and higher specificity compared to previous studies. Different cutoff points would improve the performance to detect patients with more severe OSAS.
Keywords: Obstructive Sleep Apnea; Polysomnography; Surveys and Questionnaires